Taming your dragon addressing your technical debt - Brown, Andrew Richard (Apress, 2024)
Technical debt is an often-overlooked problem that the software industry needs to take more seriously. All organizations are impacted by it, most wish that they had less of it, but need help in understanding the nature of the beast. This book aims to clear up any misconceptions and show you how to implement a sound technical debt management program to suit your company's needs. You'll learn the greatest challenge in solving the technical debt dilemma is not to find solutions to it, but rather to find solutions to the human and organizational issues that lead to that debt. For example, convincing senior stakeholders of the importance of addressing technical debt, getting stakeholders to acknowledge how their actions lead to unintentional debt, and enabling teams to prioritize technical debt over short-term goals. Therefore, this book is divided into three parts: defining technical debt, understanding technical debt, and tackling technical debt. It begins by explaining why technical debt should not be considered a technical problem, but rather a problem of how trade-off decisions are made. You'll then examine how making decisions using the affect heuristic, more commonly known as a "gut feeling," can lead to unnecessary technical debt, followed by some techniques for combating your vulnerability to this trap. Reducing your organization's level of technical debt is not easy. Taming Your Dragon will show you how to implement a technical debt management program. What You Will Learn Review a new paradigm based on technical debt being a combination of trade-off problems and system problems Understand the many ways that technical debt adversely affects an organization's ability to deliver IT change Create an effective process for addressing technical debt See why analogies are important Who This Book Is For Software teams supporting DevOps, managers, and other business stakeholders looking to implement a technical debt management program.